2020
DOI: 10.1021/acsami.0c10799
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Surface Coating of LiNbO3 on High-Ni Layered Cathode Materials for Lithium-Ion Batteries

Abstract: High-Ni cathode materials with a layered structure generally suffer from structural instability induced by a highly reactive Ni component, especially at the surface. Crystalline LiNbO 3 , with excellent thermal stability and ionic conductivity, has the potential to considerably enhance the interfacial stability of these cathode materials. By optimizing the crystalline coating of bifunctional LiNbO 3 on a high-Ni cathode material, we are able to improve cycle performance and rate capability by minimizing the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…The modifications of LNMO and other cathode materials [e.g., LiMn 2 O 4 , LiCoO 2 , LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811)] with a coating of LiNbO 3 can improve the cycle performance and enhance the overall charge capacity of these materials. ,, In principle, LiNbO 3 is an excellent solid electrolyte with a high thermal and chemical stability, as well as a low charge transfer resistance. , The degree of crystallinity of the LiNbO 3 determines whether the coating can successfully suppress the detrimental structural changes to the cathode materials that can result from the intercalation and deintercalation of Li ions during electrochemical cycling. , Although the neutralization of free radicals or adverse chemical species (e.g., HF and/or residual alkali compounds) does not require the coating to have a uniform coverage over the particle, the coatings that serve as a physically protective layer often do require complete coverage of the particles . Prior art has indicated that ultrathin, uniform LiNbO 3 coatings (e.g., <10 nm in thickness) exhibit a relatively low charge transfer impedance, a high Li diffusivity, and an improved protection from structural collapse .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The modifications of LNMO and other cathode materials [e.g., LiMn 2 O 4 , LiCoO 2 , LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811)] with a coating of LiNbO 3 can improve the cycle performance and enhance the overall charge capacity of these materials. ,, In principle, LiNbO 3 is an excellent solid electrolyte with a high thermal and chemical stability, as well as a low charge transfer resistance. , The degree of crystallinity of the LiNbO 3 determines whether the coating can successfully suppress the detrimental structural changes to the cathode materials that can result from the intercalation and deintercalation of Li ions during electrochemical cycling. , Although the neutralization of free radicals or adverse chemical species (e.g., HF and/or residual alkali compounds) does not require the coating to have a uniform coverage over the particle, the coatings that serve as a physically protective layer often do require complete coverage of the particles . Prior art has indicated that ultrathin, uniform LiNbO 3 coatings (e.g., <10 nm in thickness) exhibit a relatively low charge transfer impedance, a high Li diffusivity, and an improved protection from structural collapse .…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics contribute to the lower discharge capacity observed for the LiNbO 3 -coated LNMO particles (122 mAh/g) than that of the as-prepared LNMO particles (130 mAh/g) after the 100 charge–discharge cycles at a rate of 1C (Figure S19). The crystallinity of the coating is also an important factor that dictates the performance of the coating in response to mechanical and thermal stresses . The presence of amorphous domains in the coatings could also contribute to the relatively lower performance of the coated LNMO particles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, secondary or primary particles of LiNi x Co y Mn 1– x – y O 2 cathodes have been coated or recombined with chemically stable compounds (Al 2 O 3 , WO 3 , Li 3 PO 4 , LiNbO 3 , and LiAlO 2 ) to prevent the bulk material from electrolyte erosion and prolong the life span. Actually, it is trouble to generate an adequately uniform coating layer to serve as a firewall against corrosion from the organic electrolyte, and the sophisticated coating procedure also hampers its industrial application. Alternatively, bulk doping with Nb, Zr, Mg, W, Na, F, and so forth in a transition metal layer or an oxygen layer has also been extensively reported. Taking Zr 4+ substitution for instance, lattice Zr 4+ shows a stronger oxygen binding capacity than Ni 2+/3+ , Co 3+ , and Mn 4+ , leading to a stable transition metal layer .…”
Section: Introductionmentioning
confidence: 99%